Solusi Atas Kesulitan Guru dalam Mengajarkan Materi PKN di SD - Komala Sari Harahap; Lia Sintia; Enjelyn Agria Siagian (Lembaga Penelitian dan Pengabdian Masyarakat, 2024)
Civics has an important role in shaping students’character and morals.Ethics comes from greek,meaning moral character or custom.Ethics are values regarding moral judgment. The library research method is carriedout by collecting data from various written sources. Problems in civies learning are complex, they can come the curriculum, teacher,students may face limited educational resources,and another.teachers may not be interested in civics material.